PENERAPAN MODEL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKATKAN HASIL BELAJAR IPAS DI SEKOLAH DASAR - Paris Naofel Ramadhan; Serly Safitri; Yanti Fitria; Arwin Arwin (Jurnal Manajemen Pendidikan, 2026)
This study aims to improve student learning outcomes in science subjects through the implementation of the Numbered Heads Together (NHT) model at SDN 01 Bandar Buat. The main problem in this study is the low learning achievement where 57.14% of students have not reached the KKTP, which indicates a systemic problem in the form of passive attitudes and uneven participation. Method: This Classroom Action Research (CAR) was conducted in two cycles on 28 fifth grade students. Data were collected through activity observations and learning outcome tests. Results: The implementation of the NHT model significantly improved learning outcomes, marked by an increase in the class average score from 74.00 in cycle I to 83.00 in cycle II. Teacher and student activities also showed consistent progress to reach the very good category. Novelty: This study shows that individual responsibility structured in the NHT model is effective in minimizing systemic problems such as passive attitudes and inequality in student participation in science learning integrated into the Independent Curriculum.